الجرائم الدولية الخاضعة للاختصاص الفعلي للمحكمة الجنائية الدولية - مكائيل تميم (Latakia University Journal - Economic and Legal Sciences Series, 2018)
International crime is a crime of international law that threatens the international order, affects the interests of the protected persons under the rules of this law, the gravity of the damage caused by it to the supreme interests of the international community. In terms of the result, many regulations and legal regulations have been issued for many international courts, followed by other special courts, which comply with the same rules as the previous international courts, which required international legalization to protect individuals from any transaction that could affect them. Criminalization of certain acts which are considered international crimes such as crimes against humanity and war crimes, grave breaches of the Geneva Conventions of 1949 and genocide. In fact, in the light of these facts, international crimes can be classified into three categories: category I: international crimes committed by individuals as members of a State against international law persons only, such as the crime of aggression. Category II: International crimes committed by individuals as members of a State against a particular group on national, racial or religious grounds such as the crime of genocide and the crime of racial discrimination. Third category: International crimes committed by individuals in their private capacity such as the crime of trafficking in women and slaves and the crime of counterfeiting foreign currency. إن الجريمة الدولية هي جريمة من جرائم القانون الدولي، تهدد النظام الدولي، و تمس مصالح محمية بمقتضى قواعد هذا القانون، و تتسم بجسامة الضرر الناجم عن وقوعه على المصالح العليا للجماعة الدولية[1] . من حيث النتيجة, تم إصدار العديد من اللوائح و الأنظمة القانونية للعديد من المحاكم الدولية، تلتها محاكم خاصة أخرى، مستوفية في لوائحها نفس ما تضمنته سابقتها من المحاكم الدولية و التي أوجبت وضع تقنين دولي يحمي الأفراد من كل تعامل يمكن أن يمسهم و ذلك عن طريق تجريم بعض الأفعال و التي تعتبر جرائم دولية كالجرائم ضد الإنسانية و جرائم الحرب، و الانتهاكات الجسيمة لاتفاقيات جنيف لعام 1949 و جرائم الإبادة الجماعية[1]. في الحقيقة, في ضوء هذه الحقائق أصبح بالإمكان تصنيف الجرائم الدولية على ثلاثة فئات: الفئة الأولى: الجرائم الدولية التي يرتكبها الأفراد بصفتهم أعضاء دولة ضد أشخاص القانون الدولي من الدول فقط, مثل جريمة العدوان. الفئة الثانية: الجرائم الدولية التي يرتكبها الأفراد بصفتهم أعضاء دولة ضد جماعة معينة بدوافع قومية أو عنصرية أو دينية مثل جريمة الإبادة الجماعية و جريمة التمييز العنصري. الفئة الثالثة: الجرائم الدولية التي يرتكبها الأفراد بصفتهم الخاصة كجريمة الاتجار بالنساء و الرقيق و جريمة تزييف العملة الأجنبية[1].